Finite element analysis and experimental study on the deformation characteristics of lock ring. (2020) - Gurusamy, P.; Hari Krishna Raj, S.; Devarajan, S.; Dinesh Kumar, S.; Mahesh, R.; Subash, P.
Abstract: This paper discusses about the analysis of 49″ Earth Movers lock ring. This lock ring is made up of medium carbon steel (S43C) where the carbon present in the percentage of 0.4–0.46. Lock rings is the final piece of the assembly of Wheel and it holds the all components of the Wheel such as Flanges, Bead seat Ring, Rim base & Gutter. In order to work properly, the lock ring requires proper mating parts, so you must always ensure that the correct gutter section and bead seat band are used. In the 49″ inch EM Lock ring Stiffness is quite less due to diameter is large. While more than 4–5 times the lock ring is dissemble and assemble stiffness of the ring is reduced as result as air is being leak from the tire. To prevent this issue, it is planned to do the heat treatment analysis for the ring. By doing Hardening process the mechanical properties of the material is altered. The metal is heated up to 200 °C for 150 min then the metal is exposed to atmosphere for cooling process. After the Hardening process materials properties are checked by using Ansys Software. As the result of material stiffness is improved & have an ability to withstand for 10–15 times of assemble & dissemble.